Decomposition Analysis of Earnings Inequality in Rural India: 2004-2012 - Shantanu Khanna; Deepti Goel; René Morissette (Institute for the Study of Labor (IZA), 2016)
We analyze the changes in earnings of paid workers (wage earners) in rural India from 2004/05 to 2011/12. Real earnings increased at all percentiles, and the percentage increase was larger at the lower end. Consequently, earnings inequality declined. Recentered Influence Function decompositions show that throughout the earnings distribution, except at the very top, both changes in 'worker characteristics' and in 'returns to these characteristics' increased earnings, with the latter having played a bigger role. Decompositions of inequality measures reveal that although the change in characteristics had an inequality increasing effect, chiefly attributable to increased education levels, inequality declined because workers at lower quantiles experienced greater improvements in returns to their characteristics than those at the top.
Keywords: J30; J31; O53; 330; earnings; inequality; earnings distribution; rural India